O crime passional na visão do infrator privado de liberdade: um estudo em Angola - Gaspar, Maria Simone Álvaro do Céu (2015)
The crime of passion is a sociocultural phenomenon that affects public health. It is the act of extreme violence between couples, which occurs when the individual is taken by a sense of passion and intense emotion, going berserk in a situation of threat or loss of the object of love. The field of interest of this research is understanding the motivations for carrying out the crime of passion, the perceptions upon the act on individuals deprived of liberty, the insight into the emotional aspects linked to the crime committed, and the comprehension of offenders perception about the prison experience. Survey participants were offenders who committed the crime of passion against intimate partners, and were imprisoned in a detention facility in Viana, Angola. This study has a qualitative nature, utilizing a semi-structured interview as a research tool. The sample selected for the survey included 17 male participants, among which four were awaiting trial and thirteen had already been convicted. The age of respondents ranged between 26 and 54 years old. Categories were defined after the analysis of the contents of interviews. The theoretical approach was the psychodynamic psychology, which helped us understand the behavior of the subjects. The results revealed that the main reasons pushing the individuals to the crime of passion were jealousy and betrayal arisen by the presence of a rival, real or imaginary, stimulating the subject to evoke a mixture of thoughts, feelings, emotions and behaviors that aroused in him lack of control, intolerance and frustration, mobilizing him to the act of extreme violence